EMOTION REGULATION AND ATTENTION DEFICIT HYPERACTIVITY SYMPTOMS IN UNIVERSITY STUDENTS: A MEDIATING ROLE OF INTERPERSONAL PROBLEMS - Mushtaq, Rehana; Saleem, Sadia; Zahra, Sayyeda Taskeen (Journal of Postgraduate Medical Institute, 2022)
Objective: This study aims to explore the mediating role of interpersonal problems between emotion regulation and attention deficit hyperactivity symptoms in young adults. Methodology: This cross-sectional research was carried out from September 2020 to November 2020 in the city of Lahore. A sample of 1190 university students (545 men and 645 women) selected through a multi-stage sampling technique with age range18-24 years (M=20, SD=1.55) were given a Demographic Performa, Difficulties in Emotion Regulation Scale (DERS), Interpersonal Difficulties Scale (IDS), and Attention Defecit and Hyperactive Symptoms Scale (ADHSS). Results: The sample size consisted of 46% men and 54% women selected from BS1 (34%), BS2 (25%), BS3 (24%) and BS4 (17%). Pearson Product Moment correlation was used to investigate the relationship among study variables. Correlation analysis indicated that a significant moderate and high positive relationship between difficulties in emotion regulation and interpersonal problems (r=.56, p<.001), difficulties in emotion regulation and attention defecit hyperactivity symptoms (r=.36, p<.001), and interpersonal problems and attention defecit hyperactivity symptoms (r=.51, p<.001). Furthermore, mediation analysis revealed that interpersonal problems partially mediate the relationship between difficulties in emotion regulation and attention defecit hyperactivity symptoms in young adults. Conclusion: This research provides empirical evidence that interpersonal relationship problems partially mediate the relationship between emotion regulation and attention defecit hyperactivity symptoms.